CONSTITUTIONAL GOVERNMENT FOR WATER POLICY PLANNING IN IRAQ: A COMPARATIVE STUDY - Asst. Lect. Ali Majeed Khalil (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
There is no doubt that the Iraqi legislature possessed a huge amount of legislation before the year 2003, but the development that took place after this date necessitated the issuance of a set of water legislations for two reasons: The first: the drought that affected the cities of Iraq due to what is known as global warming, which calls for a greater abundance of water. The second: the interests of countries change, and this calls for reviewing water agreements to issue a set of internal legislations to ensure the optimal distribution of water resources. It is based on that that the legislator must issue appropriate legislation and enter into international agreements, and this will be discussed in detail in this research and to find out whether the Iraqi legislator was successful in organizing water policy or not, as we will answer a question that is; What is the success of the Iraqi legislature in regulating water wealth in entering? And how to deal with the countries of the source in ensuring the rights of the Iraqi water? To answer this, we are developing a plan consisting of two topics, the first is devoted to defining the water policy in Iraq, while the second topic devotes the substantive scope of water policy legislation in Iraq, and then the research ends with a conclusion that includes the most important results and proposals.